Determination Of Mechanical Properties Of Concrete With Partial Replacement of Tire Rubber Crumb - Sim, Jian Qin (2018)
The use of waste tire rubber crumb as fine aggregate can be useful for improvement of the concrete mechanism. At the same time reduce the usage of neutral resources and environmental impact the caused of concrete construction. In this research waste tire rubber were used to study the effectiveness of concrete with replacement of tire rubber crumb were prepared by replacing by 11%, 13% 15% and 17% of fine aggregate by the volume of the aggregate needed in the concrete mix. The concrete cubes were constructed in size of 150 X 150 X 150 (mm) and test under compressive strength test. The ductility of the concrete are studied by getting the deformation of the cube through dial gauge and plotted the stress strain curve. The workability , compressive strength and the ductility ratio are discussed in this research. RC11 showed the most increase in the slump value further increase in the percentage of rubber crumb may lead to further drop in the slump value and eventually fail below the required range for slump. The compressive strength of RCC achieved a lower compressive strength compared with the control sample. At 28 days, the control sample achieved an average of 24.32 MPa while the RCC get an average of 20.97MPa, 19.15MPa, 18.87MPa and 16.87MPa for RC11, RC13, RC15 and RC17 respectively. When the percentage of rubber crumb replacement increase the compressive strength of the concrete cube will decrease. This proved that the replacement of fine aggregate cube with rubber crumb will decrease the compressive strength of the concrete cube. The concrete cube with higher percentage of rubber crumb replacement had higher strain compared to the concrete cube with lover percentage of rubber crumb replacement. All of the concrete cube with rubber crumb replacement obtained a higher strain than the control sample.